Sistema de medidas como práticas socioculturais em matemáticas: - PEREIRA, Aline de Sousa (Universidade Federal do Tocantins, 2023)
This work, results of investigations carried out on the open market the Municipal Market Araguaína through an ethnographic qualitative research. The methodological procedures used were as follows: site visit the fair, open dialogue with the market traders, literature, field research based on the research of socio-cultural practices of quantities and measures commonly used by market traders interrelating them with measurement systems standard International Unit System (SI). To that end, we try to elucidate the research question: What are the units of measurement commonly used by market traders of the municipal market Araguaína? For job enrichment, it took some readings for the purpose of better understanding, as D'Ambrosio (2005), Mendes; Farias (2014) among others. This work aims to show the units of measure used by stallholders from the perspective of Ethnomatematics, once we understand the fairs is not only a place of interaction between customers and merchants, but also by promoting an important environment that can be used for the teaching and learning of mathematics.